2008
DOI: 10.3317/jraas.2008.018
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and local effects of angiotensin II blockade in experimental diabetic nephropathy

Abstract: Introduction. Our objective was to evaluate the effect of blocking the renin-angiotensin system (RAS) on the expression of transforming growth factor-beta 1 (TGF-β1), platelet derived growth factor-B (PDGF-B), tumour necrosis factor-alpha (TNF-α) and vascular endothelial growth factor (VEGF) in diabetic kidney glomeruli. Materials and Method. 1) Uninephrectomised streptozotocin induced diabetic rats were treated during eight months with vehicle (CD) or irbesartan (ID). Uninephrectomised non-diabetic rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…[29][30][31][32] Likewise, experimental models demonstrated that locally produced ANG II in the kidney may induce proteinuria via reduction of nephrin expression and podocyte injury and stimulated expression of some cytokines such as VEGF. [33][34][35] These findings suggest that local RAS activation in kidney may contribute to the pathogenesis of proteinuria in women with preeclampsia. However, the study was cross-sectional, and therefore no causal conclusion could be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Likewise, experimental models demonstrated that locally produced ANG II in the kidney may induce proteinuria via reduction of nephrin expression and podocyte injury and stimulated expression of some cytokines such as VEGF. [33][34][35] These findings suggest that local RAS activation in kidney may contribute to the pathogenesis of proteinuria in women with preeclampsia. However, the study was cross-sectional, and therefore no causal conclusion could be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of PKC (a downstream mediator of Ang II which enhances the dose of both VEGF and TGF-β) by ruboxistaurin reduced both VEGF and TGF-β expression, ameliorating albuminuria and glomerulosclerosis [36]. Ang II not only upregulates VEGF and TGF-β expression, it also upregulates platelet-derived growth factor and tumour necrosis factor, growth factors also associated with diabetic nephropathy and proteinuria [37]. Irbesartan, an Ang II antagonist, blocked the increase in expression of all of these growth factors in glomeruli of uninephrectomised, streptozotocin-induced diabetic rats [37].…”
Section: Vegf Regulation In Glomerulopathologiesmentioning
confidence: 99%
“…RAS blockers have a significant impact on the rate of decline of GFR in CKD patients with proteinuria [70][71][72] . They exert their action through many mechanisms including their hemodynamic effect on glomerular tuft pressure [73,74] , inhibition of cytokine overproduction [75][76][77][78][79] , increased serum and tissue angiotensin 1-7 [80][81][82] and stimulation of Klotho gene expression in CKD patients. The RAS-mediated renal damage might be through Klotho gene manipulation [54] .…”
Section: Pathogenesismentioning
confidence: 99%